2012
DOI: 10.1128/jvi.01998-12
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Protective Cellular Immunity Revealed by Analysis of Population-Level Immune Escape Pathways in HIV-1

Abstract: i HLA class I-associated polymorphisms identified at the population level mark viral sites under immune pressure by individual HLA alleles. As such, analysis of their distribution, frequency, location, statistical strength, sequence conservation, and other properties offers a unique perspective from which to identify correlates of protective cellular immunity. We analyzed HLA-associated HIV-1 subtype B polymorphisms in 1,888 treatment-naïve, chronically infected individuals using phylogenetically informed meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
266
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(290 citation statements)
references
References 121 publications
(191 reference statements)
22
266
1
Order By: Relevance
“…HLA-associated polymorphisms derived from the International HIV Adaptation Collaborative (IHAC) cohort, comprising 1,888 treatmentnaive individuals with chronic clade B infection from Canada, the United States, and Western Australia (16), identified by identical methods, were used for comparison. The IHAC cohort comprises predominantly Caucasian individuals, with Asians making up less than 5% of the total.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…HLA-associated polymorphisms derived from the International HIV Adaptation Collaborative (IHAC) cohort, comprising 1,888 treatmentnaive individuals with chronic clade B infection from Canada, the United States, and Western Australia (16), identified by identical methods, were used for comparison. The IHAC cohort comprises predominantly Caucasian individuals, with Asians making up less than 5% of the total.…”
Section: Methodsmentioning
confidence: 99%
“…HLA-APs can be identified in large cross-sectional linked data sets of host (HLA) and HIV genotypes using statistical-association approaches that identify viral polymorphisms significantly over-or underrepresented in individuals harboring a specific HLA class I allele (1,2,4,(16)(17)(18)21). HLA-APs that are overrepresented in individuals harboring the relevant HLA are commonly referred to as "adapted" forms, while those underrepresented in individuals harboring the relevant HLA are referred to as "nonadapted" forms (2,18).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the presence of variable epitopes in immunogens encompassing the native proteins can result in immunodominance (i.e., hierarchical recognition of some epitopes in the vaccine over others) with the generation of immunodominant T cell responses targeting non-protective epitopes that do not contribute significantly to viral control and can easily mutate without impairing viral fitness, and facilitating the propagation of functionally fit escape mutants. HLA represents a major force driving the evolution and diversification of HIV-1 within individuals and at the population level 2628 with recognition of immunodominant but non-protective epitopes. It has been suggested that variable sequences can serve as immunodominant “decoys” that can absorb immune reactivity, driving the emergence of escape mutations and potentially precluding responses against conserved protective epitopes.…”
Section: Introductionmentioning
confidence: 99%